The Pengaruh Mata Pelajaran Kewirausahaan dan Dukungan Orang Tua Terhadap Minat Berwirausaha Siswa SMK Labschool 1 Unesa Jurusan Bisnis Digital: Pengaruh Mata Pelajaran Kewirausahaan dan Dukungan Orang Tua Terhadap Minat Berwirausaha Siswa SMK Labschool 1 Unesa Jurusan Bisnis Digital - Aristanta, Rafverga; Cahya, Septyan Budy (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to investigate the effect of: 1) Entrepreneurship Education on students' Entrepreneurial Interest at SMK Labschool Unesa, and 2) Parental Support on students' Entrepreneurial Interest at SMK Labschool Unesa. This type of research is quantitative. The population in this study consists of all students of class XI and XII majoring in Digital Business. The research sample comprises 54 students, selected through a purposive sampling technique (saturated sample). Data were collected through questionnaires using a likert scale that had been tested for validity and reliability. Data analysis using multiple linier regression analysis. The results show that: 1) Entrepreneurship Subjects (X1) and Parental Support (X2) have a significant positive effect on the Entrepreneurial Interest of SMK Labschool 1 Unesa students, this can be seen from the results of multiple linear regression on X1 of 0,330 and X2 of 0,052. 2) The partial test (T-test) obtained a significance value of 0,004 for variable X1 and 0,000 for variable X2, or less than 0,05. Meanwhile, the simultaneous test (F-test) obtained a significance value of 0,001 or less than 0,05. This means that Ha is accepted and H0 is rejected, so Entrepreneurship Subjects (X1) and Parental Support (X2) have a significant effect on Entrepreneurial Interest (Y) among SMK Labschool 1 Unesa students, Digital Business Department.